Rancang Bangun Sistem Pelayanan Surat Berbasis Web dengan Penerapan Tanda Tangan Digital di Nagari Bukit Bais - Mukhtarijal Mukhtarijal; Hadi Kurnia Saputra; Dony Novaliendry; Ahmaddul Hadi (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
Administrative letter services at the village (nagari) level are still largely conducted using conventional methods, resulting in various issues such as limited service hours, slow processing times, and risks of document loss. This study aims to develop a web-based letter service system with the implementation of digital signatures in Nagari Bukit Bais to improve efficiency, security, and transparency of public services. The research adopts the Agile Development method with an iterative approach, including requirement analysis, system design, implementation, and testing. The developed system enables citizens to submit requests online and is equipped with features such as officer verification, digital signing by the village head, automatic notifications, digital archiving, and document verification using QR Codes. Security mechanisms are implemented using SHA-256 cryptographic hashing and RSA-2048 digital signature algorithms, supported by X.509 digital certificates. Functional testing using end-to-end methods shows that all system features operate successfully without failures, while non-functional testing confirms the reliability of document security and integrity. The resulting system is able to automate the entire service process, reduce processing time, and ensure document authenticity and security. Therefore, this system can serve as a solution to support the digital transformation of public services at the village level.